2016
DOI: 10.1017/brimp.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognitive Interventions in Neuropsychiatric Patients: A Meta-Analysis

Abstract: Social cognitive deficits are common in neuropsychiatric disorders. Given the proximity of social cognition (SC) to everyday functioning, many intervention studies (including targeted, comprehensive, and broad-based approaches) have focussed on SC. The aim of this paper was to quantitatively meta-analyse the efficacy of SC interventions in adult neuropsychiatric patients. Databases Pubmed, PsycINFO, Web of Knowledge, and Embase were searched for controlled SC intervention studies published between 01-01-2003 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 156 publications
(206 reference statements)
2
26
0
3
Order By: Relevance
“…It may be that the lack of awareness of other mental agents that is associated with the restricted and repetitive behaviors of ASD increases the intrinsic degree of correlation in a child’s activity that then does not allow for a flexible coordination with another person in a social interaction. Children then may be less able to coordinate with another person due to their lack of flexibility, which makes it harder for them to build rapport [ 10 13 ] and in turn manifests itself as a deficit in theory of mind known to be part of ASD [ 40 , 41 , 44 , 45 ]. Importantly, the fact that the dynamic whole-body movement measures are related to higher social cognition measures indicates that these high functioning children with ASD are showing some degree of embodied social competence in the sense that the level of their social cognition seems to manifest itself also in their whole-body movements during this type of interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that the lack of awareness of other mental agents that is associated with the restricted and repetitive behaviors of ASD increases the intrinsic degree of correlation in a child’s activity that then does not allow for a flexible coordination with another person in a social interaction. Children then may be less able to coordinate with another person due to their lack of flexibility, which makes it harder for them to build rapport [ 10 13 ] and in turn manifests itself as a deficit in theory of mind known to be part of ASD [ 40 , 41 , 44 , 45 ]. Importantly, the fact that the dynamic whole-body movement measures are related to higher social cognition measures indicates that these high functioning children with ASD are showing some degree of embodied social competence in the sense that the level of their social cognition seems to manifest itself also in their whole-body movements during this type of interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have claimed that lack of ToM does not explain all deficits present in ASD, is not unique to ASD, and is not universally experienced by all individuals with ASD [ 42 , 43 ]. However, ToM remains a central measure used in the ASD literature to classify children [ 41 , 44 , 45 ] and there is some consensus that there is evidence that the development of ToM is delayed in children with ASD and the attribution of mental states is challenging for individuals with ASD, even if they do pass ToM tests [ 43 ]. The current study employed four ToM tasks, three that required verbal answers and one non-verbal measure.…”
Section: Introductionmentioning
confidence: 99%
“…Although social-cognitive interventions do exist, these have generally been trialed in adult patients with clinical populations including schizophrenia, autism spectrum disorder, or acquired brain injury. 34 Future research could work to adapt these interventions for a pediatric CNS tumor population.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment has been conducted with a range of approaches from a singular treatment focused on a particular skill to more comprehensive approaches targeting two or more such skills and possibly also non-social cognition. As reported in this volume, Roelofs Wingbermühle, Egger, & Kessels (2017) conducted a meta-analysis of 41 studies reporting on treatment of social cognitive disorders in over 1500 patients with acquired brain disorders or neuropsychiatric symptoms. Encouragingly, they found that targeted treatments were especially effective, particularly for emotion perception, ToM and social perception (the ability to use social cues to determine social roles, rules, etc).…”
Section: The Push For Rehabilitation Of Social Cognitionmentioning
confidence: 99%
“…Clinicians who work with people with brain disorders, whether these are developmental, psychiatric or due to acquired injury or disease, are only too aware that social and emotional impairments are a major obstacle to successful psychosocial functioning. Social cognition impairments not only characterise disorders of schizophrenia, but are also seen as the defining characteristic of Autism Spectrum Disorders (American Psychiatric Association, 2013) and manifest in other intellectual and genetic developmental disabilities (Roelofs, Wingbermühle, Kessels, & Egger, 2017). In the field of traumatic brain injury (TBI), 84% of clinicians reported that disorders of social cognition affect at least half of their clients (Kelly, McDonald, & Frith, 2016).…”
mentioning
confidence: 99%